INFLUENCE OF THE POLYVITAMINIC COMPLEX INTAKE ON THE VITAMIN PROVISION OF THE KINDERGARTNERS - V.M. Kodentsova; O.A. Vrzhesinskaya; A.A. Sokol'nikov (Вопросы современной педиатрии)
The researchers examined how well the children aged between 3–5 years old were provided with с, В1, В2, В6 and РР vitamins both before and after 3 months of taking in two forms of the polyvitaminic complex (syrup and pastilles). The examination was performed on the basis of the renal excretion of the ascorbic acid, thiamine, riboflavin, 4cpiridoxyl acid and 1cmetylnicotinamide. The polyvitaminic complex intake led to increase of excretion of all the examined vitamins apart from the ascorbic acid, warned about the deterioration of provision with с and в6 vitamins and some what improved children's provision with В1, В2 and РР vitamins. However, the intake of this complex in the applied doses didn't ensure complete normalization of the vitamin status indices among all the examined children, which indicates the necessity to apply it in bigger doses, as the manufacturing firm recommends to.Key words: vitamins, polyvitamin, polyvitaminic complexes, hourly renal excretion, children.